KINERJA PENYULUH PERTANIAN DALAM PENGEMBANGAN SUMBERDAYA MANUSIA PETANI DI DESA TOUNELET KECAMATAN SONDER - Rivaldi Novel Turangan; Benu Olfie Suzana; Elsje Pauline Manginsela (Sam Ratulangi University, 2019)
The purpose of this study is to describe the Performance of Agricultural Extension in the Development of Farmer Human Resources. This research was conducted in Tounelet Village, Sonder District, Minahasa District for 3 (three) months conducted in April to June 2018. Primary data was obtained directly from interviews with farmers, extension agents, agriculture, fisheries and forestry (BP3K) sub-districts of Sonder using questionnaires. Secondary data was obtained from the local government and the Sonder District Agricultural, Fisheries and Forestry Extension Agency (BP3K), there were books available at local bookstores and the internet through the Google search engine, Google Scholar to access scientific journal articles and thesis related to the topic of this research as well as various information about the performance of extension agents for the development of farmers' human resources and assessment of the performance of extension agents. The results showed that the performance value of agricultural extension agents, according to the criteria of Ruky (2001), reached 517, which meant that the performance of extension agents was sufficient.*erprm*